Bioactivity of gallic acid–conjugated silica nanoparticles against Paenibacillus larvae and their host, Apis mellifera honeybee - Domínguez, Enzo (2019)
The aim of this work was to evaluate antimicrobial activity against Paenibacillus larvae and oral toxicity against workers and larvae of Apis mellifera of gallic acid (GA) and two nanohybrids of GA and silica. Also, the physicochemical, structural, and energetic properties of GA and the nanohybrids were determined through structure–activity relationship (SAR). The minimum inhibitory concentration (MIC) against P. larvae was determined. GA showed MIC values between 62.5 and 125 μg/ml, whereas the nanoparticle functionalized through the GA carboxylic moiety (NP2) showed the best antimicrobial activity with a MIC value of 23 μg GA/ml for four of the five isolates used. SAR analysis showed that electronegativity, chemical hardness, and dipolar moment are reliable estimators of the antimicrobial activity. NP2 showed the lowest toxicity against workers and was innocuous for bee larvae. Therefore, the nanohybrid NP2 was the best antibacterial and resulted in non-toxic against workers and larvae of honeybees, becoming a potentially effective and safe agent for the treatment of American Foulbrood disease.